CORRELATION BETWEEN LEARNING STYLES AND STUDENTS‟ ACADEMIC ACHIEVEMENT IN SPEAKING SKILL IN ENGLISH DEPARTMENT AT HASANUDDIN UNIVERSITY - Astri, Zul (JURNAL ILMU BUDAYA, 2014)
Students are individuals with individual needs, interests and methods of processing information.This research aims to elaborate the correlation between learning styles and students‘ academicachievement in speaking skill and explains how well the teaching material and classroomactivities fulfill the needs of students with different learning styles. The respondents of this studyare 30 students of English Department students of academic year 2009/2010. The researcherconducted One-Group Pretest-Posttest design where there is only one group experiment that isgiven pre-test and post-test. In gathering the data, questionnaire, classroom observation, pre, andpost tests are applied. Questionnaire is to know their basic learning style in general. Next,classroom observation is to see and find out students‘ attitude, classroom activities and classroomparticipations. Pre-test is to see their basic speaking skill before the class started and they aregiven learning activities. In addition, post-test is to measure students‘ speaking skill after they aregiven learning activities by teacher. The result of the research shows that 36, 8 % visual learnerscan improve their skill after learning activities are given. Moreover, auditory learners are clearlyseen that they are sophisticated speakers and listeners so in this speaking class they can showtheir ability and it is proved from the data that 83, 3 % auditory learners have increased speakingskill. Furthermore, the learning activities also appropriate for tactile and visual- auditorylearners because 100 % of tactile and visual auditory learners can improve their speakingskill after learning activities are conducted in the classroom.Keywords: Learning style, Material, and English Speaking Skill.